ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT MENONTON FILM BIOSKOP: STUDI KASUS KOTA BATAM - Hendrawan, Hendrawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Watching movies in the cinema is often done by the people of Batam. There are many cinema places that people visit to watch movies. This study aims to determine the effect of film quality, brand image, attractiveness, word of mouth on the intention to watch films in Batam city cinemas. In the quantitative research, 400 respondents will be taken and in the qualitative research, 30 respondents will be taken. In this study used disproportionate random sampling and multiple regression methods. The application used for data processing is in the form of IBM SPSS statistics 24. From the results of testing on the hypothesis which states that there is a significant influence on the results obtained by the variables Film Quality, Brand Image, Attractiveness, and Word of mouth have a positive effect on viewing interest in the Batam community.